Regulation of transepithelial ion transport in the rat late distal colon by the sympathetic nervous system - Zhang, X; Li, Y; Zhang, X; Duan, Z; Zhu, J (Physiological research, 2015)
The colorectum (late distal colon) is innervated by the sympathetic nervous system, and many colorectal diseases are related to disorders of the sympathetic nervous system. The sympathetic regulation of colorectal ion transport is rarely reported. The present study aims to investigate the effect of norepinephrine (NE) in the normal and catecholamine-depleted condition to clarify the regulation of the sympathetic adrenergic system in ion transport in the rat colorectum. NE-induced ion transport in the rats colorectum was measured by short-circuit current (I(sc)) recording; the expression of beta-adrenoceptors and NE transporter (NET) were quantified by real-time PCR, and western blotting. When the endogenous catecholamine was depleted by reserpine, the baseline I(sc) in the colorectum was increased significantly comparing to controls. NE evoked downward deltaI(sc) in colorectum of treated rats was 1.8-fold of controls. The expression of beta(2)-adrenoceptor protein in the colorectal mucosa was greater than the control, though the mRNA level was reduced. However, NET expression was significantly lower in catecholamine-depleted rats compared to the controls. In conclusion, the sympathetic nervous system plays an important role in regulating basal ion transport in the colorectum. Disorders of sympathetic neurotransmitters result in abnormal ion transport, beta-adrenoceptor and NET are involved in the process.
Keywords: inhibitory vychytávání adrenergních neurotransmiterů; Receptors, Adrenergic, beta-2; kolon; Sympathomimetics; Adrenergic Uptake Inhibitors; techniky in vitro; messenger RNA; proteiny přenášející noradrenalin přes plazmatickou membránu; střevní sliznice; Ion Transport; epitelové buňky; sympatický nervový systém; Colon; Norepinephrine Plasma Membrane Transport Proteins; zvířata; Norepinephrine; časové faktory; RNA, Messenger; potkani Sprague-Dawley; Epithelial Cells; Male; sympatomimetika; In Vitro Techniques; iontový transport; Rats, Sprague-Dawley; noradrenalin; Animals; Membrane Potentials; mužské pohlaví; Sympathetic Nervous System; membránové potenciály; Intestinal Mucosa; Time Factors; beta-2-adrenergní receptory